Teachers’ Pedagogical Beliefs and Classroom Practices in Teaching Science - Yodel D. Dizon (Future Science / FSH-PH Publications, 2026)
The study aimed to determine the teachers’ pedagogical beliefs and classroom practices among elementary schools in Zone II, Division of Zambales. A descriptive research design was employed using a survey questionnaire as the primary instrument for data collection. Descriptive and inferential statistics were used to analyze and interpret the data. Findings revealed that the majority of the teacher-respondents were female, in middle adulthood, with MAED units, holding the position of Teacher I, and relatively new in the service. The respondents strongly agreed on both teacher-centered and student-centered pedagogical beliefs. Results further showed that there was no significant difference in teachers’ pedagogical beliefs and classroom practices in teaching science when grouped according to profile variables. However, a significant relationship was found between teachers’ pedagogical beliefs and their classroom practices, indicating a high correlation between the two. The effective use of strategies to reduce teachers’ and students’ resistance in science teaching requires purposeful developmental planning and the integration of active learning strategies. Moreover, the integration of technology in classroom instruction has the potential to promote more student-centered and constructivist beliefs among teachers. The study recommends that teachers employ differentiated activities and teaching strategies based on students’ learning needs and conduct action research to further improve the teaching and learning process. Future researchers are encouraged to conduct broader and more in-depth studies to validate the findings.